Toxoptera citricidus (Kirkaldy,1907) (HEMIPTERA : APHIDIDAE) : aspectos biológicos e respostas às ações de bioinseticidas - Gambarra, Wanessa Porto Tito (2015)
Aphids are important pests in agriculture, mainly because they are vectors of phyto-pathogenic virus. One of the ways to control these insects, is the use of botanical insecticides. However in order to the control to be effective it is also necessary to know their biological characteristics. In this context, the aim of the present study was to evaluate the bioactivity of several plant extracts upon Toxoptera citricidus, presently considered one of the most important pests of citric plantations. For this purpose its life cycle has been studies and important metabolic processes as: consumption, production, respiration and excretion were quantified. Based on these data the species life table and energy budget were constructed. The bioactivity of 11 species of plants including a nanoformulation of the neen, Azadirachta indica, was evaluated through acute toxicity tests. T. citricidus was maintained on Citrus limonia under controlled constant conditions in the laboratory. Among these 5 had insecticide activity upon T. citricidus causing mortality to 80 % of the individuals tested or more. The lethal median concentration (CL50 48h) varied from 0.17 to 4.10 mg/mL for the nynphal phases and from 0.30 to 5.01 mg/mL to adults thus evidencing insecticide properties and presenting high to be used in the management of this pest. A magnetic nuclear ressonance of honeydew, the excretion product of this aphid, evidenced the presence of important aminoacids besides carbohydrates allowing an advance in the knowledge on aphid-ants and aphid- host plant. The total energy budget of of T. citricidus varied According to the aphid age. Mean daily energy consumption were 0.3717 cal for nymphs and 0.4761cal for adults. The energy fraction invested in production by T. citricidus was high, with a mean value around 60%, evidencing high efficiency of energy retention. It was concluded that considering its biological characteristics T. citricidus has a relevant role in the energy transference across the ecosystem.